Teknik Penerjemahan Amplifikasi Dalam Takarir Film “Gintama Live Action” Karya Hideaki Sorachi - Adriansyah, Marcellino; Mulya, Komara (Universitas Negeri Jakarta, 2022)
This study aims to determine the form and function of the amplification translation technique in the subtitle of the film